From Community College to University: Institutionalization and Neoliberalism in British Columbia and Alberta - Levin, John S.; Aliyeva, Aida; Walker, Laurencia (Canadian Journal of Higher Education, 2016)
This qualitative investigation of higher education institutional development addresses new universities that were former community colleges in the provinces of British Columbia and Alberta. Stemming from an original study conducted nearly two decades earlier, this investigation’s data were collected from the same institutions and from similar sources: institutional documents, government policies, and interviews from faculty and administrators; thus, qualifying as a longitudinal qualitative investigation. This investigation explains institutional instability and identity change as a result of new government policies and institutional norms during the period of 2000-2013. Future research can monitor the influence of neoliberal practices on the development of these new model higher education institutions in the Canadian context.